An international comparison of phase angle standards between the novel impedance bridges of CMI, INRIM and METAS. (8th June 2018) - Ortolano, Massimo; Palafox, Luis; Kučera, Jan; Callegaro, Luca; D'Elia, Vincenzo; Marzano, Martina; Overney, Frédéric; Gülmez, Gülay
Abstract: We report here the results of a comparison of electrical impedance standards aimed at evaluating four novel digital impedance bridges developed by the national metrology institutes CMI, INRIM and METAS. This comparison, which is the first of its kind, involved phase angle impedance standards developed by TÜBITAK UME with phase angles of ± and ±, and magnitudes ranging from about 100 Ω to 1 MΩ. The comparison demonstrated agreement among the measurement results obtained with the different bridges, and allowed us to gather information on the stability of the phase standards and on more critical aspects related to the characterization of the bridges.